Research of the stamping process of “coupling” component billet using DEFORM program. - Каразей, В.Д.; Соколан, К.С.; Решетник, П.П. (Problems of Tribology, 2017)
Designing technological processes using modern CAD/CAM/CAE systems allows reducing costs that can appear during production process, since there is a possibility of more precise forecasting of defects of different type, which are con-nected with imperfect technology. It gives a possibility to study processes of metal deformation under different types of in-strument movement by changing friction conditions, plasticity model and rheological characteristics of the material. DEFORM program is intended for analysis of three-dimensional yield of metal under different process of metal forming op-eration. Usage of the program gives a possibility to forecast the character of metal forming during forming operation, and due to this fact, costs of experimental researches are considerably reduced. Using DEFORM program allows to research changes of movement and stresses values that appeared depending on time of process running. Key words: extruding, forming operation, modelling, stamping punch.